2000
DOI: 10.1093/nar/28.10.2084
|View full text |Cite
|
Sign up to set email alerts
|

Codon usage in Chlamydia trachomatis is the result of strand-specific mutational biases and a complex pattern of selective forces

Abstract: The patterns of synonymous codon choices of the completely sequenced genome of the bacterium Chlamydia trachomatis were analysed. We found that the most important source of variation among the genes results from whether the sequence is located on the leading or lagging strand of replication, resulting in an over representation of G or C, respectively. This can be explained by different mutational biases associated to the different enzymes that replicate each strand. Next we found that most highly expressed seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
3
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(115 citation statements)
references
References 38 publications
7
103
3
2
Order By: Relevance
“…Finally, contrary to results reported for several bacteria (McInerney 1998;Lafay et al 1999;Romero et al 2000), we found that the position of each sequence in the leading (53.6% of the total) or in the lagging strand of replication does not affect the codon choices. This is probably due to the fact that this genome is characterized by a very weak GC skew.…”
Section: Codon Usagecontrasting
confidence: 99%
See 2 more Smart Citations
“…Finally, contrary to results reported for several bacteria (McInerney 1998;Lafay et al 1999;Romero et al 2000), we found that the position of each sequence in the leading (53.6% of the total) or in the lagging strand of replication does not affect the codon choices. This is probably due to the fact that this genome is characterized by a very weak GC skew.…”
Section: Codon Usagecontrasting
confidence: 99%
“…Indeed, in nearly all quartets there is an increase in G-ending codons and a decrease in C-ending triplets as long as hydrophobicity increases (de Miranda et al 1999). A rather complex pattern was reported for Chlamydia trachomatis, where codon choices are the result of strand-specific mutational biases, natural selection acting at the level of translation, the hydropathy level of each protein, and amino acid conservation (Romero et al 2000). Finally, in Helicobacter pylori, although the genome composition is not skewed and there is a low level of heterogeneity among genes, codon usage seems to be influenced neither by simple mutational biases nor by translational selection (Lafay et al 2000).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Compositional strand bias is relatively homogeneous in the genome and is especially strong at third codon positions, as expected from a mutational bias (Lobry, 1996a;McLean et al, 1998;Rocha et al, 1999a). In highly biased genomes, strand bias is the major force shaping codon usage (McInerney, 1998;Romero et al, 2000). In these cases, one can easily discriminate the position of the genes relative to the replicating strand based on their codon usage or amino acid content of the respective proteins (Lafay et al, 1999;Mackiewicz et al, 1999;Rocha et al, 1999a).…”
Section: Compositional Strand Biasmentioning
confidence: 99%
“…In most cases, the leading strand in replication is rich in guanosine (G) and thymidine (T) and the lagging strand is rich in cytosine (C) and adenosine (A), resulting in sequences having GC and AT skews. Replication orientation significantly affects gene sequences, independent of any coding biases, such as from amino acid or codon preferences (Rocha et al 1999;Lafay et al 1999;Tillier and Collins 2000;Romero et al 2000).…”
Section: Introductionmentioning
confidence: 99%